Keamanan E-Voting Di Indonesia Melalui Pemanfaatan Kriptografi Pada Sistem AES (Advance Encryption Standard) - Fefiana Diny Hermawati; Muhlis Tahir; Muafa Syaifurrohman; Muzayyanatul Hikmah; Jaya Abadi Amroin; Mochamad Bahruddin; Irsyad Irsyad (Pusat Riset dan Inovasi Nasional, 2023)
As a democratic country, voting is a mandatory and routine agenda for our country when choosing leaders in an organization to the state level. The paper-based voting system that has been used so far has several weaknesses such as ballot damage, vote counting errors, susceptibility to fraud, and delayed election results. To overcome these issues, a more secure and guaranteed electronic voting system is needed. The shift from conventional media to various media used for opinion polling, such as social media/internet, has occurred in this technological era. The E-Voting system has been confirmed as safe and in line with the latest technological advancements. To enhance its security level, the system can use various types of cryptographic algorithms, including AES. Cryptography can be the solution in maintaining information security such as confidentiality, data integrity, non-repudiation, and authentication